2020
DOI: 10.1002/etc.4808
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Behavioral Toxicity of Tributyltin in the Tropical Guppy Poecilia vivipara

Abstract: The tropical estuarine guppy Poecilia vivipara was used to address fish early life stage toxicity caused by the antifouling contaminant tributyltin. Six-day-old P. vivipara were exposed for 7 d to control water and waterborne tributyltin at 15.8, 83.8, 716, and 818 ng tin (Sn) L-1. After exposure, swimming, feeding, growth, and eye histological endpoints were evaluated. Histopathological analysis of the retinal pigment epithelium (RPE) indicated alterations in pigment positioning at all tributyltin concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Similar to our observation, TBT exposure has been reported to cause degenerative changes in the corneal epithelium, lens, pigment layer of the retina, and choroid of minnow Phoxinus larvae, eventually resulting in the opaque color of the eyes (Fent and Meier, 1992) [8] . When Tropical Guppy (Poecilia vivipara) was exposed to TBT (15.8-818 ng Sn/L) for 7 days, the retinal pigment epithelium was altered in pigment positioning, the photoreceptor layer was disorganized, and iris melanin was hyperpigmented (de Paulo et al, 2020) [5] . Mild histological changes in the eye of zebrafish in the present study might be attributed to a lower concentration of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our observation, TBT exposure has been reported to cause degenerative changes in the corneal epithelium, lens, pigment layer of the retina, and choroid of minnow Phoxinus larvae, eventually resulting in the opaque color of the eyes (Fent and Meier, 1992) [8] . When Tropical Guppy (Poecilia vivipara) was exposed to TBT (15.8-818 ng Sn/L) for 7 days, the retinal pigment epithelium was altered in pigment positioning, the photoreceptor layer was disorganized, and iris melanin was hyperpigmented (de Paulo et al, 2020) [5] . Mild histological changes in the eye of zebrafish in the present study might be attributed to a lower concentration of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2021) [23] examined the effects of oxidative stress on behavior in the brains and eyes of TBT-exposed medaka and observed that superoxide dismutase (SOD) and catalase (CAT) activity were adversely affected by decreased locomotor activity and social interaction. Following TBT exposure to the tropical guppy (Poecilia vivipara) de Paulo et al (2020) [5] found significant changes in retinal and corneal structure and organization. Various studies have been conducted related to TBT exposure in aquatic animals, but there is a need to evaluate its effect on the eyes following long-term exposure at various concentrations in zebrafish, which is considered an aquatic animal model that has retinal layers similar to humans.…”
Section: Introductionmentioning
confidence: 99%